Use of medicinal plants in Taiçoca de Fora, Nossa Senhora do Socorro, Sergipe, Brazil - Mendonça, Marcus Aurélio D’Alencar; Correia, Maiko dos Santos; Santos, Matheus Ismerim Silva; São Mateus, Fabrício Pimentel; Soyinka, Marcelino (SITIENTIBUS série Ciências Biológicas, 2010)
This study presents the ethnobotanical of medicinal plants used by the residents of the village Taiçoca de Fora, located at the municipality of Nossa Senhora do Socorro, Sergipe State, Northeastern Brazil. Data were collected through the fieldwork carried out from July to September 2002. After selection of key informants, a semi-structured questionnaire about botanical aspects and uses of reported plants was submitted. There were recorded 28 species distributed among 17 families, and the most cited were “boldo” or “sete-dor” (Plectranthus barbatus), “erva-cidreira” (Melissa officinalis), “capim-santo” (Cymbopogon citratus) and “sambacaitá” (Hyptis pectinata). It was also noted that the preparation is mainly by decoction of leaves for the treatment of diarrhea and inflammation in general and as a sedative.